2012
DOI: 10.1103/physreva.86.012509
|View full text |Cite
|
Sign up to set email alerts
|

L-shell x-ray emission from neonlike W64+

Abstract: We present high-resolution crystal spectroscopy measurements of the n = 3 → n = 2 L-shell x-ray transitions of neonlike W 64+ , which include seven electric dipole allowed transitions, two electric quadrupole transitions, and one magnetic quadrupole transition. The resulting wavelength data are compared to recent calculational results, allowing us to clearly distinguish between different theoretical approaches, which need to take into account not only substantial electron correlations effects but also radiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 80 publications
12
52
0
Order By: Relevance
“…Detailed laboratory measurements on tungsten ions are well suited for electron beam ion traps (EBITs), where charge-state selection is good and the ion temperature and electron density low. Several studies of tungsten in various ionization stages and spectral ranges have been conducted using EBITs; see, e.g., [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Although designed to have a very wide electron-beam energy range, EBITs have mostly been used at energies above several hundred electron volts, leading to a focus on highly or moderately charged ions with little attention on the first few charge states.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed laboratory measurements on tungsten ions are well suited for electron beam ion traps (EBITs), where charge-state selection is good and the ion temperature and electron density low. Several studies of tungsten in various ionization stages and spectral ranges have been conducted using EBITs; see, e.g., [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Although designed to have a very wide electron-beam energy range, EBITs have mostly been used at energies above several hundred electron volts, leading to a focus on highly or moderately charged ions with little attention on the first few charge states.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, several experimental works (see, e.g. [6][7][8][9] and the references therein) on the tungsten ions are published. Alongside there is a considerable interest in multicharged ions from theoreticians.…”
Section: Introductionmentioning
confidence: 99%
“…Beiersdorfer et al [21] reported high-resolution crystal spectroscopy measurements and identified ten lines in neon-like W 64+ arising due to the n = 3→n = 2 L-shell X-ray transitions as electron to the n = 3 level was considered. In case of the O-like W 66+ ion, a number of transitions between levels with n = 2 and n = 3 were investigated.…”
Section: L-shell Excitation Of Mg-through O-like Tungsten Ionsmentioning
confidence: 99%
“…X-ray spectroscopy utilizing emissions from L-shell as well as M-shell tungsten ions is an attractive option for tokomak plasma diagnostics [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The temperature of the ITER core will be sufficiently high to produce the L-shell tungsten ionic charged states.…”
mentioning
confidence: 99%
See 1 more Smart Citation